2014
DOI: 10.1177/1071100714530884
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Lower Limb Cast Immobilization on Calf Muscle Pump Function

Abstract: Background: We have investigated the role of the calf muscle pump in casted patients. An audit of venous thromboembolism (VTE) in casted patients showed that the thrombosis occurred in the casted leg; this has not been previously assessed. We postulated that local factors play a major role, and we set out to assess the calf muscle pump in casted patients and to determine whether this can be optimized despite below-knee cast immobilization. Methods: We measured the flow in the popliteal vein using a validated m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 14 publications
0
16
0
Order By: Relevance
“…This is the first study to examine the effects of active toe movement on DVT in patients with foot and ankle trauma treated with cast. Although we have previously shown that active toe movement (AToM) can influence calf pump function in healthy volunteers with below knee casts applied, we were unable to find any evidence that this reduces the incidence of DVT [8]. We anticipated that patients who performed regular active toe movements would have had improved venous calf pump function parameters, however this intervention had no significant effect.…”
Section: Discussionmentioning
confidence: 80%
See 3 more Smart Citations
“…This is the first study to examine the effects of active toe movement on DVT in patients with foot and ankle trauma treated with cast. Although we have previously shown that active toe movement (AToM) can influence calf pump function in healthy volunteers with below knee casts applied, we were unable to find any evidence that this reduces the incidence of DVT [8]. We anticipated that patients who performed regular active toe movements would have had improved venous calf pump function parameters, however this intervention had no significant effect.…”
Section: Discussionmentioning
confidence: 80%
“…Considering that active toe movement influences venous haemodynamics in healthy volunteers to a similar extent to intermittent pneumatic compression foot pump devices, we anticipated that this may also reduce asymptomatic DVT in patients with casts [8,21]. One of the main reasons why AToM failed to reduce DVT rates may relate to the relative infrequent performance of exercises by patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The minimum hemodynamic effect of a device intervention to be DVT preventive is unknown. However, studies on hemodynamics during foot dorsiflexion may provide baseline data on blood flow during normal mobilization showing around at least a twofold increase in peak velocity, with results varying according to the type of exercise and body posture . Moreover, it is generally accepted that increased venous return leads to improved DVT prevention by correcting one of the three pathophysiological factors of thrombosis, the stasis, the other two being endothelial damage and increased coagulability, collectively known as the Virchow's triad.…”
Section: Discussionmentioning
confidence: 99%